Role of gut symbionts of insect pests: A novel target for insect-pest control - Rupawate, Pravara S.; Roylawar, Praveen; Khandagale, Kiran; Gawande, Suresh; Ade, Avinash B.; Jaiswal, Durgesh Kumar; Borgave, Seema (Frontiers in Microbiology, 2023)
Insects possess beneficial and nuisance values in the context of the agricultural sector and human life around them. An ensemble of gut symbionts empowers insects to adapt to diverse and extreme environments and to occupy every available niche on earth. Microbial symbiosis helps host insects by supplementing essential diet elements, providing protection from predators and parasitoids through camouflage, modulation of a signalling pathway to achieve homeostasis and trigger boosting immunity against pathogens, hijacking plant pathways to circumvent plant defence, acquiring the capability to degrade chemical pesticides and degradation of harmful pesticides. Thus, microbial protection strategy may lead to the overpopulation of insect pests which can reduce crop yield drastically. Some studies have demonstrated enhanced insect mortality via the destruction of insect gut symbionts; through the antibiotic application approach. The review summarises various roles played by the gut microbiota of pest insects and a few studies carried out on pest control via targeting the symbionts. Manipulation or exploitation of the gut symbionts alters the host insect growth and population and consequently is a potential target for developing better pest control strategies. Methods like modulation of gut symbionts via CRISPR/Cas9, RNAi and combining IIT and SIT to enhance insect mortality are discussed further. In the ongoing scenario of insect pest management, gut symbionts prove to be the most reliable, eco-friendly and novel approach to integrated pest management.